Non-diabetic Out-Patients’ Lifestyle and Awareness of Type 2 Diabetes Symptoms in two Nigerian Secondary Health Care Facilities - Eze, Uchenna I.H; Osoba, Doyin O; Iheanacho, Chinonyerem O (International Journal of Human and Health Sciences (IJHHS), 2021)
Objectives: Diabetes is a highly prevalent, lifestyle-related, but preventable chronic disease in parts of Nigeria. The study assessed lifestyle and awareness of non-diabetics on diabetes for effective primary prevention. Materials and methods: A cross-sectional survey was conducted on non-diabetic out-patients in two hospitals using a structured questionnaire. Descriptive analyses were performed using SPSS version 21.0. Outcome variables were presence of unhealthy diet and classical diabetes symptoms in the respondents. p≤0.05. Results and discussion: A total of 300 respondents participated in the study. Majority 186(62.0%) had never monitored their blood glucose. Over half 168(56%), were not aware of diabetes preventive measures, and few, reported the occurrence of diabetic symptoms with fatigue having the highest occurrence 61(20.3%), followed by blurred vision 58(19.3%). Age (p=0.229), Marital status (p=0.375), Education (p=0.217), Income (p=0.240), were not associated with diabetic symptoms. Majority did not smoke 262(87.3%) or take alcohol 216(72.0%). Conclusion: Low awareness of diabetes was mostly found among the respondents. Majority was not aware of diabetes symptoms and had never checked their blood glucose. However, healthy social lifestyle was found among them. Findings indicate the need for enhanced diabetes education to non-diabetic patients. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 446-453